An autonomous robotic arm for efficient rock collection in uncharted territories - Deshmukh, Sanjay; Thakker, Bhaumik Hitesh; Gupte, Vedangi Nilesh; Kapadia, Taher Kutbuddin (Indonesian Journal of Electrical Engineering and Computer Science, 2024)
The autonomous rock collector using robotic arm for exploration of unknown territories (ARCAxUT) is introduced as an innovative solution for the efficient retrieval of rock samples in unexplored space regions. Traditional, human-reliant methods are costly and hazardous, prompting the development of ARCAxUT. Equipped with a smart robotic arm, an RGB-D camera, and NUC computer, the system autonomously detects and estimates the mass of various rock samples. Validated in simulated and real-world environments, the algorithm ensures precise gripper control, achieving an impressive 95.4% accuracy in rock size estimation. This breakthrough offers transformative capabilities for space missions, revolutionizing celestial body sample collection and advancing broader societal implications in space exploration technologies.